Access to Medicines and Vaccines Implementing Flexibilities Under Intellectual Property Law - Correa, Carlos M.; Hilty, Reto M. (Springer Nature, 2022)
This open access book is the outcome of a Global Forum on Innovation, Intellectual Property and Access to Medicines held in December 2019 at the Max Plank Instititute in Munich, organised by the South Centre and the Max Plank Institute. The academics and experts from international organisations participating have contributed chapters to this book. The book is for policy makers (in Ministries of Health, Ministries of Trade, Ministries of Foreign Affairs, patent offices), but also relevant for academics (law, trade, public health), on the flexibilities available in the Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization to promote access to medicines.